1989
DOI: 10.1093/ptj/69.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulation in the Relief of Primary Dysmenorrhea

Abstract: The purpose of this study was to replicate a previous study to determine the effectiveness of acupuncture-like transcutaneous electrical nerve stimulation in treating primary dysmenorrhea. Twenty-one women with dysmenorrhea received a placebo pill or 30 minutes of acupuncture-like TENS. All subjects completed two pain questionnaires before treatment; immediately posttreatment; 30, 60, 120, and 180 minutes posttreatment; and the next morning upon awakening. Each woman also participated in a separate study measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 15 publications
0
19
0
3
Order By: Relevance
“…To ensure an electrical nerve stimulation without pain and fear, transcutaneous delivery of the stimulation is often adopted in clinical research and application, including obstetrics and gynecology for pain relief during labor (12) or dysmenorrhea (13). To our knowledge, TEAS has not been reported to be used to improve the clinical efficacy of ET.…”
mentioning
confidence: 99%
“…To ensure an electrical nerve stimulation without pain and fear, transcutaneous delivery of the stimulation is often adopted in clinical research and application, including obstetrics and gynecology for pain relief during labor (12) or dysmenorrhea (13). To our knowledge, TEAS has not been reported to be used to improve the clinical efficacy of ET.…”
mentioning
confidence: 99%
“…In an early study, Klein and Litt (1981) found that only 14.5% American adolescents had ever consulted their physicians for help with their cramps. Current treatments for dysmenorrhea include analgesic medication (Campbell & McGrath, 1997;Lethaby, Augood, & Duckett, 1999), oral contraceptives (Milsom, Hedner, & Mannheimer, 1994), topical heat patches (Akin et al, 2001), acupressure (Chang & Jun, 2003;Chen & Chen, 2004), acupuncture (Helms, 1987), spinal manipulation (Kokjohn, Schmid, Triano, & Brennan,1992), transcutaneous electrical nerve stimulation (TENS) (Kaplan, Rabinerson, Lurie, Peled, Royburt, & Neri, 1997;Lewers, Clelland, Jackson, Varner, & Bergman, 1998), herbal medicine (Kotani et al, 1997), and exercise (Golomb et al, 1998).…”
mentioning
confidence: 99%
“…28 Six RCTs offered no discernible physiologic rationale. [23][24][25]31,35,38 The number of rationales in the included trials is summarized in Table 3.…”
Section: Resultsmentioning
confidence: 99%